Toward a 10-W level femtosecond erbium laser operating in the 1600 nm low gain region - Haolin Yang; Ruili Zhang; Sailing He (APL Photonics)
1.6 µm ultrafast lasers are important in biomedical applications because the wavelength is located within an attractive biological window called the near-infrared-II (NIR-II) region. However, for erbium- or thulium-doped fibers, 1.6 μm is not their typical gain wavelength; therefore, realizing a high power femtosecond (fs) 1.6 μm laser is a challenging task. In this work, we propose a pump scheme assisted by a C-band laser. The new pump scheme can improve the gain at 1.6 μm with a mechanism originating from the re-absorption effect of the ground state and the in-band relaxation between the splitting energy levels 4I13/2b and 4I13/2a. Applying the pump scheme to the all-fiber large-mode-area (LMA) chirped pulse amplification (CPA) system, we achieve a record-high output power of ∼9.42 W, corresponding to a 262 nJ single pulse energy. The pulse duration after compression is ∼361 fs. Our approach of combining a LMA CPA system with a C-band auxiliary laser co-pumping scheme opens a way to increase the output power of an erbium-doped fiber laser by one order of magnitude in the 1600 nm region, even though this is a low gain region.